Prognostic Value of Inflammatory Biochemical Markers (IL-8, PCT, CRP) for Cardiovascular Disease in Patients with Pancreatitis: Biochemical Markers Predicting CVD in Pancreatitis - Yang, Zaili; Cui, Dejun; Li, Fei; Huang, Bo; Liu, Qi (Journal of Medical Biochemistry, 2025)
Background: Patients with pancreatitis may be at increased risk of cardiovascular disease (CVD), but the biochemical mechanisms underlying this risk are not fully defined. Inflammatory biomarkers may provide valuable prognostic information.Methods: We retrospectively analyzed 180 patients with pancreatitis (Jan 2021–Dec 2023). Serum levels of interleukin-8 (IL-8), procalcitonin (PCT), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) were quantified using enzyme-linked immunosorbent assay (ELISA) and routine laboratory tests. Logistic regression was applied to identify independent biochemical predictors of CVD, and a risk prediction model was developed and validated using ROC curve analysis.Results: IL-8, PCT, CRP, and age emerged as independent predictors of CVD occurrence in pancreatitis patients (all P
Keywords: pancreatitis; cardiovascular disease; inflammatory biomarkers; clinical biochemistry; prediction model